contestada

Which subtraction expression has the difference 1 + 4i? (–2 + 6i) – (1 – 2i) (–2 + 6i) – (–1 – 2i) (3 + 5i) – (2 – i) (3 + 5i) – (2 + i)

Respuesta :

Answer:

(3 + 5i) – (2 + i)

Step-by-step explanation:

(–2 + 6i) – (1 – 2i)

The real parts  -2-1 = -3

The imaginary parts 6i--2i = 6i+2i = 8i

(–2 + 6i) – (–1 – 2i)

The real parts -2 +1 = -1

The imaginary parts 6i --2i = 6i+2i =8i

(3 + 5i) – (2 – i)

The real parts 3-2 =1

The imaginary parts = 5i --i = 5i+i = 6i

(3 + 5i) – (2 + i)

The real parts 3-2 =1

The imaginary parts 5i -i = 4i

Answer:

d.(3 + 5i) – (2 + i)

Step-by-step explanation: